THE WELFARE OF ORPHANAGE CHILDREN AND ITS IMPLICATION FOR SOCIAL WORK PRACTICE - Yuka, Vivian A.; Omorogiuwa, Tracy B.E. (EBSU Journal of Social Sciences and Humanities, 2024)
This study examined the welfare services available to orphanage children in Edo State, andsocialworkinterventiontoamelioratetheirchallenges.Previous research has documented the appalling conditions that orphans and other vulnerable children endure due to abuse, exploitation, violence, and neglect. The study looked at how non-governmental organizations may help the OVC, and it found that this is not only important but also a sign of a good response from society to the crisis, despite the government's inability to provide orphans with a comprehensive and practical framework that is focused on the community. Therefore, in order to improve the wellbeing of orphans, social work engagement is necessary. The study's sample size consists of one hundred orphans from five (5) different orphanage settings. The study used a survey research methodology, and the structured questionnaire served as the primary data gathering tool. A basic random sample technique was also used. Descriptive statistics such as mean and standard deviation were used to analyze the data that was gathered for the study. According to research, there are numerous environmental risks to an orphan's survival and health. The government, non-governmental organizations, and social workers were the main sources of information on orphan vulnerability in order to mobilize the public at all levels of advocacy and to provide the basic necessities. To disseminate educated messages regarding orphans, both civil and media attention are required.